British playwrights, 1956-1995 : a research and production sourcebook - Demastes, William W. (Gale virtual reference library., 1996)
Chronicles the history of British theater from 1956 to 1995 by providing detailed information about the playwrights of that period. Entries include information such as biographical information, the production history for particular plays, a survey of the playwright's critical reception, and an assessment of the dramatist's work.